AQP-9, KCNJ11 and ABCC8 Gene Variants in Open Angle Glaucoma: A Hypothesis - Thumann, Gabriele; Sorgente, Nino (Journal of Ophthalmology and Research, 2021)
Importance: Primary open angle glaucoma, an age-related, retinal neurodegenerative disease of unknown etiology, is treated by lowering intraocular pressure, even though elevated intraocular pressure is present in only about 60% of patients. Since we found that tolbutamide, which inhibits the opening of ATP-sensitive potassium channels, modulates aqueous dynamics with a significant increase in outflow, and since aquaporin-9 is essential for retinal ganglion cells survival, gene variants coding for the ATP-sensitive potassium channels and aquaporin-9 may participate in the development and progression of glaucoma. Objective: To identify gene variants involved in ion and water transport in the trabecular meshwork of glaucoma donors. Design: The study is a gene association study; since gene variants can be somatic or germline, the following genes KCNJ8, KCNJ11, ABCC8, and ABCC9, QP1, AQP4, AQP9, ATP1A1, KCNMA11, and CLCN3 associated to ATP-sensitive potassium channels and water transport in the trabecular meshwork were sequenced from DNA isolated from trabecular meshwork of glaucoma donors. Setting: The study is a gene association study carried out with samples obtained through the Cooperative Human Tissue Network of which the DNA was isolated by the technical personnel at the Lions Vision Gift eye bank and analyzed by Admera Health LLC. Participants: The only criteria for the ten donors (5 male, 5 females; 70-91 years of age) in the study was a diagnosis of primary open angle glaucoma and a consent form signed at their lifetime or by responsible relatives. Main Outcomes and Measures: Of several missense variants, one was found in all 10 and three were found in nine trabecular meshwork samples. All variants, whether synonymous or missense, were germline. Results: The AQP9 mi